Neoantigen peptide-pulsed dendritic cell vaccine therapy after surgical treatment of pancreatic cancer: a retrospective study - Oyama, Koki; Nakata, Kohei; Abe, Toshiya; Hirotaka, Kento; Fujimori, Nao; Kiyotani, Kazuma; Iwamoto, Chika; Ikenaga, Naoki; Morisaki, Shinji; Umebayashi, Masayo; Tanaka, Hiroto; Koya, Norihiro; et al. (Frontiers in Immunology, 2025)
IntroductionPancreatic cancer shows very poor prognosis and high resistance to conventional standard chemotherapy and immunotherapy; therefore, the development of new breakthrough therapies is highly desirable.MethodWe retrospectively evaluated the safety and efficacy of neoantigen peptide-pulsed dendritic cell (Neo-P DC) vaccine therapy after surgical treatment of pancreatic cancer.ResultThe result showed induction of neoantigen-specific T cells in 13 (81.3%) of the 16 patients who received Neo-P DC vaccines. In survival analysis of the nine patients who received Neo-P DC vaccines after recurrence, longer overall survival was observed in patients with neoantigen-specific T cell induction than those without T cell induction. Notably, only one of the seven patients who received Neo-P DC vaccines as adjuvant setting developed recurrence, and no patient died during median follow-up 61 months after surgery (range, 25-70 months). Furthermore, TCR repertoire analyses were performed in a case treated with Neo-P DC vaccine combined with long and short peptides, and one significantly dominant clone induced by the long peptide was detected among CD4+ T cell populations.DiscussionThe present study suggests the feasibility and efficacy of Neo-P DC vaccine therapy after surgical treatment of pancreatic cancer in both postoperative recurrence cases and adjuvant setting. A case analysis suggests the importance of combination with long peptides targeting CD4+ T cell.